Misdiagnosed gastric diverticulum as a left adrenal lesion on imaging - Jing‐Yan Zhang; Chenchen Qian; Chun‐Wu Pan (Clinical Case Reports, 2024)
Key Clinical Message Gastric diverticulum in the posterior wall of the stomach is very rare, and it is easy to be misdiagnosed as a left adrenal mass on imaging. Therefore, we must consider the possibility of gastric diverticulum when diagnosing a left adrenal mass. Abstract This paper reports a case of gastric diverticulum that was misdiagnosed as a left adrenal mass on abdominal enhanced CT. The patient underwent laparoscopic adrenalectomy, but there was no mass in the left adrenal found during surgery. After the incision of the retroperitoneum, a cystic mass was found adjacent to the posterior gastric wall which turned out to be gastric diverticulum. This case suggests that gastric diverticulum, a rare disease, may be interpreted as an adrenal mass on imaging. Therefore, as a urologist, the gastric diverticulum must be excluded when CT suggests a mass in the left adrenal region.